Digital Image Confidentiality using New Encryption Method - Yaseen Hikmat Ismaiel; Omar Muayad Abdullah; Yasir Ali Mahmood (SISTEMASI, 2026)
The significant development in mobile phone cameras, in terms of the clarity and high-resolution images captured, the wide utilizing of mobile phones and other communication devices among all segments of society, and the increasing use of social networking sites and the exchange of millions of digital photos daily, all have been pointed with a great importance of digital images and the need to provide adequate security and protection for these images. Digital images contain a large amount of information and recently they have an effective and easy tools of communication without the need for a determined text.Given that digital images contain important, personal, and sensitive information, there is a great need to protect these images and prevent unauthorized persons from applying any changes to the image's contents. There is a great deal of work in this field, most of which uses encryption methods to achieve this protection. As is well known, there are two types of encryption systems (symmetric and asymmetric). Symmetric encryption systems are fast but require a secret key distribution process, while asymmetric encryption systems are relatively slow, involving complex processes. Therefore, they are not suitable for use in social networking applications that require rapid performance and interaction. In this research, a proposed method for digital image encryption is proposed, which includes the use of logical XOR operation to encrypt the digital image based on two proposed levels with scrambling operation to provide a high degree of diffusion and confusion for the resulting encrypted image. The proposed method was evaluated through a set of efficiency measurement metrics (NPCR, UACI, MSE, PSNR, SSIM, Entropy, and Correlation) and it gave results showed a difference between the original image and the image resulting from the first level of encryption. We also noted that the image resulting from the second level had a higher percentage of difference and randomness compared to the original image. Therefore, the proposed encryption method is suitable in terms of speed and confidentiality for use in encrypting digital images and thus maintaining their privacy.